Analisis kesalahan dalam soal-soal pemecahan masalah siswa SMA kelas XI pada materi barisan dan deret aritmatika ditinjau dari teori newman - Saqinah Fauziah Noer; Asep Ikin Sugandi; Risma Amelia (IKIP Siliwangi, 2023)
This study focused on analyzing student errors in problem solving questions in terms of Newman's theory on questions in the subject matter of Arithmetic Sequences and Series. The subjects in this study were 10 students of class XI IPA 2 at Al-Mukhtariyah Rajamandala High School using a descriptive qualitative method. For the technical implementation, students were given questions directly in class. Based on the results of the analysis in this study, students' errors in reading error) that is equal to 62%, then an error in understanding the problem (comprehension error) that is getting a result of 60%, then an error in transforming (transformation error) that is equal to 52%, an error in the completion process stage (process skill error) is 26%, and finally an error in writing the final answer (encoding error) that is getting a percentage of 20%. If seen from the mistakes that have been made, students are still low in problem solving.